Experimental and Numerical Investigation of the Mesoscale Size Effect in Notched Woven Composites - Andrea Ferrarese; Carlo Boursier Niutta; Alberto Ciampaglia; Raffaele Ciardiello; Davide S. Paolino; Giovanni Belingardi (Applied Sciences, 2023)
The uniaxial strength of 2 × 2 twill carbon fiber-epoxy composite with circular open holes is governed by the stress concentration induced by the notch, as well as by the variation of the material response with the stress localization. In this study, these concurrent phenomena were studied using an experimental-numerical approach, considering the effect of the composite heterogeneity. An innovative simplified mesoscale model using shell elements to replicate the woven pattern was developed. The material properties of the model were identified with a data-driven optimization scheme that minimizes the difference between the experimental full-field strain, measured with Digital Image Correlation, and the one predicted by the model itself. The elastic properties identified for the material at tow level are analogous to that of a unidirectional composite, with longitudinal and transverse moduli of around 102 GPa and 15 GPa, respectively. The calibrated model was used to analyze the stress concentration and localization induced by circular notches with increasing diameter. A size effect describing the increase in the carbon fiber tow strength following the increase in stress localization was observed. The mesoscale material strength was found to increase by about 2.5 times in the presence of the notch, from 2131 to 3922 MPa in fiber direction, partially balancing the stress intensification effect of the hole that leads to an approximately three-fold stress increase in the material.